In which direction does skin move during joint movement?. Issue 2 (3rd June 2015) - Fukui, T.; Otake, Y.; Kondo, T.
Abstract : Background/ Purpose: A skin movement artifact is a major problem in three‐dimensional motion analysis. Furthermore, skin tension lines are important in plastic surgery. Skin tension depends upon the body area and the direction of resistance. From the perspective of skin continuity and clinical observation, we hypothesized that the contralateral side of the skin of the extremities moves in the opposite direction. This study aimed to examine kinematics of thigh skin including movement direction during pelvic sway. Methods: Fifteen healthy men participated in this study. Kinematic data were obtained using a three‐dimensional motion analysis system. To detect opposite skin movement, 42 markers were attached to the front, back, lateral, and medial sides of the thigh and pelvis. Front and back markers in the sagittal plane and lateral and medial markers in the frontal plane were arranged in a line connecting the hip and ankle joint centers, respectively. Subjects performed maximal pelvic movements in the anterior‐posterior and rightward‐leftward directions. Results: The results showed that the front skin of the thigh was transferred upward and that the back skin was transferred downward during pelvic anterior sway. Opposite skin movements were observed during posterior pelvic sway. We also found that the lateral skin was transferred upward and that the medial skin was transferred downward during hip adduction and vice‐versa during hip abduction. Conclusion: These findings suggest that the skin moves according to certain physiological rules.